Análisis de los factores de comercialización que están asociados al nivel de satisfacción de los clientes del Laboratorio 180º de la PUCE - Ibarra que produce y comercializa desayunos y almuerzos - Alvarez Zuleta, Javier Sebastián (2024)
The research aims to identify the marketing factors associated with customer satisfaction at the 180º Laboratory of PUCE-Ibarra, focusing on the production and marketing of breakfasts and lunches. The specific objectives include analyzing the relationship between delivery time, product quality, seller's treatment, and product promotion with customer satisfaction. The adopted methodology is a mixed approach with a non-experimental cross-sectional design, using Likert scale surveys applied to a sample of 118 individuals from a population of 380 administrative and teaching staff at PUCE-Ibarra. The results of the statistical analysis, conducted using SPSS version 25, indicate that both delivery time and product quality are positively related to customer satisfaction. The conclusions highlight the need to improve these aspects to increase customer satisfaction and loyalty, suggesting that marketing strategies should focus on optimizing delivery times and ensuring consistently high product quality.